Implementasi Algoritme Grain Sebagai Proses Enkripsi Data dan Algoritme SHA-3 Sebagai Hashing Data Pada Rancang Bangun Aplikasi Pemilu Online Berbasis Android - Arsana Yudistira; Ari Kusyanti; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
General election has become a routinity for Indonesian citizen. To hold a general election the government need to spend a lot of money . on 2014 Indonesia goverment was spent 24,1 trilion rupiah to hold general election on that year. On the other hand the increasing number of Android-based smartphone sales is continue to increase year by year. With the high number of android based smartphone sales can be use to a solution to reduce costs of hold a general election with changing the conventional election E-Votting with smartphone android. As we know that Indonesia election apply the â€œLUBERJURDILâ€ principle that means Indonesia election is direct, public, independent, confidential, honest and fair. To meet the needs of confidential principle, we need a system that can make sure the data of election are secret. Combination of grain algorithm as data encryption and SHA-3 algorithm as data hashing is the best way to secure the data. Grain can give confidentiality aspect because make the data cant read by everyone while SHA-3 give integrity aspect to participants because the data cant changed by everyone. From testing that have done before, both algorithms give 153 ms of time processing and 96,4% score of avalanche effect.